Unveiling Ontogenesis of Herbal Medicine in Plant Chemical Profiles by Infrared Macro-Fingerprinting - Xu, Chang-Hua; Liu, Su-Li; Zhao, Sheng-Nan; Li, Shou-Zhuo; Sun, Su-Qin (Planta Medica, 2013)
Given that harvesting time has a great impact on the quality of herbal medicine, knowing the ontogenesis in the chemical profile aspect is essential to determine the optimal harvesting season. A high-throughput and versatile approach (herbal infrared macro-fingerprinting) harmonizing with the character of herbal medicine and providing the whole chemical profile (entirety), group analogues (part), and single compounds (major components) is developed to rapidly disclose the variation rule of the full chemical profile of herbal medicine over a growing season without extraction pretreatments, and thus to determine the optimal harvesting period in respect to groups of chemical compounds using Scutellaria baicalensis as a demonstration. IR macro-fingerprints of Scutellaria baicalensis harvested in the same period have a high similarity (> 0.91) despite small variations, suggesting that IR macro-fingerprinting can faithfully reflect the spectacle of “disordered order” in nature. From Year-1 spring to Year-3 autumn, general contents (%, w/w) of total flavonoids fluctuate up and down with a maximum value in Year-2 spring, and that of saccharides is relatively stable except for the attenuation from Year-2 autumn to Year-3 spring. From Year-1 autumn to Year-2 spring, flavonoid aglycones initially produced in Scutellaria baicalensis are extensively transformed to responding flavonoid glycosides. From Year-2 spring to Year-3 autumn, flavonoid glycosides are converted back to their corresponding aglycones. The best seasons for collecting Scutellaria baicalensis with a high content of flavonoid glycosides and aglycones would be Year-2 spring and Year-3 spring, respectively.
Keywords: Scutellaria baicalensis Georgi; Labiatae; herbal medicine; ontogenesis; infrared spectroscopy; flavonoids; baicalin